The Role of Islamic Social Finance in Achieving the Objectives of Sustainable Development Goals (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The increased development challenges have been spreading everywhere and limiting the welfareof humanity on the earth around the globe. However, since 2015 the whole world has beenmoving towards a new global development agenda. This agenda is assumed to replace themillennium development goals (MDGs) that lapsed a few years ago (Atah, Nasr & Mohammed,2018). This new global development plan aims to achieve 17 sustainable development goals(SDGs) by 2030. The recent inclination of international efforts has been directed towardsutilizing all resources to create a sustainable world in which the present generation can meet theirneeds while preserving the rights of future generations. In other words, sustainable developmentrequires economic growth that helps remove all the development challenges such as poverty,malnutrition, hunger, unemployment, illiteracy, etc. Alike, the complexity and fast growth of thesocial and environmental challenges that are treating human life economically and socially,communities are becoming more and more vulnerable to socio-economic issues and incapable oftackling them effectively.Moreover, since creating the development plan in 2015, countries worldwide are joiningtheir efforts with combined bodies or agencies to achieve socio-economic sustainability anddevelopment by the year 2030. Recently, Islamic Social Finance has been underlined due to itsfinancial inclusion role as one of the main drivers of sustainable development amongacademicians and specialists. Then, this paper aims to explore the main perspectives in whichIslamic Social Finance plays a role in achieving SDGs. In this regard, the article discusses threemain Islamic Social Finance tools: Zakat, Awqaf, and Infaq, and their potential to cover theglobal SDGs' investment gap.